Evidence for the persistence of food web structure after amphibian extirpation in a Neotropical stream. Issue 8 (1st August 2015) - Barnum, Thomas R.; Drake, John M.; Colón-Gaud, Checo; Rugenski, Amanda T.; Frauendorf, Therese C.; Connelly, Scott; Kilham, Susan S.; Whiles, Matt R.; Lips, Karen R.; Pringle, Catherine M.
Abstract : Species losses are predicted to simplify food web structure, and disease‐driven amphibian declines in Central America offer an opportunity to test this prediction. Assessment of insect community composition, combined with gut content analyses, was used to generate periphyton–insect food webs for a Panamanian stream, both pre‐ and post‐amphibian decline. We then used network analysis to assess the effects of amphibian declines on food web structure. Although 48% of consumer taxa, including many insect taxa, were lost between pre‐ and post‐amphibian decline sampling dates, connectance declined by less than 3%. We then quantified the resilience of food web structure by calculating the number of expected cascading extirpations from the loss of tadpoles. This analysis showed the expected effects of species loss on connectance and linkage density to be more than 60% and 40%, respectively, than were actually observed. Instead, new trophic linkages in the post‐decline food web reorganized the food web topology, changing the identity of "hub" taxa, and consequently reducing the effects of amphibian declines on many food web attributes. Resilience of food web attributes was driven by a combination of changes in consumer diets, particularly those of insect predators, as well as the appearance of generalist insect consumers, suggesting that food web structure is maintained by factors independent of the original trophic linkages.